Banana and plantain production systems in Benin: ethnobotanical investigation, varietal diversity, pests, and implications for better production - Chabi, M.C.; Dassou, A.G.; Dossou-Aminou, I.N.; Ogouchoro, D.; Omondi, Bonaventure Aman Oduor; Dansi, A. (Springer, 2018)
The cultivated banana and plantain (Musa spp.) are valuable for nutritional and socio-economic security for millions of people worldwide. In Benin, banana and plantain are among the most produced, consumed, and traded commodities. Its production is mainly for local consumption and remains insufficient to the demand. However, the varietal diversity of banana and plantain cultivated in Benin is not documented. This study aims at characterizing the banana and plantain cropping systems, genetic diversity, and production constraints as a baseline to the full utilization of this resource in crop improvement and to identify the potential production and agronomic qualities. A baseline investigation of ethnobotanical attributes of banana cultivars was done in 51 randomly chosen villages in southern Benin. Interviews with randomly selected representative farmers were carried out. Key informant interviews and focus group discussions were used for global confirmatory investigation of survey data. Socio-demographic data and indigenous knowledge on the farmer uses of banana and plantain diversity, such as cultural practices, origin, and availability of banana and plantain planting materials, and the constraints and criteria of varietal preference cited by farmers were ranked. Eighty-seven locally recognized cultivars were found: 73 of banana and 14 of plantain groups. The most popular cultivars were Sotoumon (banana) (52.94%), Aloga (plantain) (41.17%), Planta (banana) (33.33%), and Adjangan (plantain) (27.45%). Of the eleven production constraints identified, the main biotic challenges were banana weevil Cosmopolites sordidus Germar and banana bunchy top virus (BBTV), while abiotic problems were drought and the wind. Some local varieties like Amandan, Assonwonnou, Coleti, and Ninkouin are extremely rare owing to agronomic and economic preference perceptions. This study provides a baseline for banana diversity in Benin and the West African region and entry points for biological characterization and production improvement. This would enable the exploitation of this resource for plant breeding towards biotic and abiotic challenges facing banana production.